Phenotypic Diversity of C. neoformans var. neoformans Clinical Isolates from Localized and Disseminated Infections - Birkenfeld, Zena M.; Dittel, Nikita; Harrer, Thomas; Stephan, Christoph; Kiderlen, Albrecht F.; Rickerts, Volker (Microorganisms, 2022)
Cryptococcus neoformans var. neoformans is the second most prevalent agent of cryptococcosis in central Europe. Infections mostly present with localized skin and disseminated infections. Previous studies did not find these presentations to be determined by the fungal genotype as detected by multilocus sequence typing (MLST). However, phenotypic fungal traits may impact clinical presentation. Here, we studied the growth and virulence factors of C. neoformans var. neoformans isolates from disseminated and localized infections and an environmental isolate. We used coincubation with Acanthamoeba castellanii and the Galleria mellonella infection model to identify phenotypic characteristics potentially associated with clinical presentation. Clinical isolates of C. neoformans var. neoformans present a substantial phenotypic variability. Median survival of Galleria mellonella varied between 6 and 14 days. C. neoformans var. neoformans isolates from disseminated infections showed stronger melanization and larger capsules. They demonstrated superior uptake into an amoeba and increased cytotoxicity for the amoeba. Differences of strains from localized and disseminated infections in coincubation with amoeba are in line with the importance of phagocytes in the pathogenesis of disseminated cryptococcosis. Phenotypic traits and non-vertebrate infection models may help understand the virulence potential of C. neoformans var. neoformans isolates.
CRIS-Team Scopus Importer:2022-02-04
Keywords: Acanthamoeba castellanii; Cryptococcosis; Cryptococcus neoformans; Galleria mellonella; Virulence factors